Precise positioning based on pixel differential in linear optical sensor array - Alsayed, Abdallah; Mahadi, Muhammad Razif (Elsevier, 2014)
Precision farming emphasis on the efficient use of resources for optimizing the output. In the production of paddy, measurement of water level and the rate of rising are important factors. Sensing techniques suffer from some restrictions which restrict obtaining high accuracy and high resolution measurements such as noise of electrical sensor, sensing clear response, potential error, and environmental effects. This paper presents a non-contact method to measure position in linear motion. Moreover, this work is going to be background and concept for water level measuring system